2020
DOI: 10.1002/mc.23261
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic potential of circulating cell‐free nuclear and mitochondrial DNA for several cancer types and nonmalignant diseases: A study on suspected cancer patients

Abstract: Circulating cell-free nuclear DNA (nDNA) has been implicated in individual cancer types with a diagnostic value; however, the role of cell-free mitochondrial DNA (mtDNA) in cancers is controversial. We aimed to investigate and compare the diagnostic potential of both nDNA and mtDNA for multiple cancers and to investigate their ability to distinguish multiple cancers from healthy controls and from nonmalignant diseases. We also investigated the prognostic value of both nDNA and mtDNA. The absolute copy number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Despite the uncertainty about the true mtDNA level introduced by the confounding factors as revealed here, we remain extremely enthusiastic about cir-mtDNA’s potential diagnostic capacity for such conditions as inflammation diseases (73), neurological disorder (35,74), trauma (75), cardiovascular diseases (76), various cancers (40,58,77,78) and, as it was seen recently, SARS-Cov2 infection (79,80). The origins of cir-exMT, exMT in EVs, and vesicles encapsulating mtDNA still need to be distinguished, as the cir-mtDNA sources may depend on the biological observation, especially with respect to the nature of the plasma preparation protocols.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Despite the uncertainty about the true mtDNA level introduced by the confounding factors as revealed here, we remain extremely enthusiastic about cir-mtDNA’s potential diagnostic capacity for such conditions as inflammation diseases (73), neurological disorder (35,74), trauma (75), cardiovascular diseases (76), various cancers (40,58,77,78) and, as it was seen recently, SARS-Cov2 infection (79,80). The origins of cir-exMT, exMT in EVs, and vesicles encapsulating mtDNA still need to be distinguished, as the cir-mtDNA sources may depend on the biological observation, especially with respect to the nature of the plasma preparation protocols.…”
Section: Discussionmentioning
confidence: 81%
“…Our study revealed that most of the authors, including ourselves, who studied this novel type of circulating biomarker previously had improperly assumed that they studied circulating fragmented mtDNA or mtDNA-associated EVs (10,3335,40,58,63,75,7779). We continue to believe, however, that highly fragmented cir-mtDNA degradation products as well as mtDNA containing EVs may have particular diagnostic relevance, despite their small proportions compared to that of cir-mtDNA deriving from exMT.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, we believe that corrective action should be taken to minimize the clinical implications of delayed cancer diagnosis, including (1) reinforcing mass screening using the fecal For this purpose, we believe that ctDNA analysis that reveals qualitative (tumor molecular profiling) or quantitative information 9,14,22,23,40 may be an ideal tool, as previously reported. 17,20,41 The diagnostic power of ctDNA would be largely improved by using a multianalyte approach. 42,43 Such a strategy would include both qualitative (such as genetic or epigenetic alterations) and quantitative (such as tissue or cell of origin or structural characteristics) markers.…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
“…We speculate that patient triage could be performed based on the quick assessment of tumor burden and the testing of biomarkers with predictive and prognosis value (such as immunohistochemistry for mismatch repair proteins; mutation analysis for KRAS, NRAS, and BRAF) . For this purpose, we believe that cirDNA analysis revealing qualitative (tumor molecular profiling) or quantitative information 8,20 21,39,13 may represent an ideal tool, as previously reported 16,19,40 .…”
Section: Discussionmentioning
confidence: 71%